Multimodel Discrete Second Order Sliding Mode Control: Stability Analysis and Real Time Application on a Chemical Reactor - Mihoub, Mohamed; Nouri, Ahmed Said; Abdennour, Ridha Ben (IntechOpen, 2011)
None